Deconstructing political Islam in Malaysia : UMNO's response to PAS' religio-political dialectic - Liow, Joseph Chin Yong (2009)
The politicisation of Islam has become a key feature of the Malaysian political terrain in recent years, and has found dominant expression in the so-called "Islamisation race" between UMNO and PAS. This paper studies the religio-political dialectics and responses that continue to define UMNO-PAS rivalry, focusing primarily on the strategies and flaws of UMNO's attempts to out-Islam PAS. It suggests that UMNO's representation of PAS as conservative fundamentalists belies the fact that the struggle to define the role of Islam in contemporary Malaysian society has created fissures within UMNO itself, resulting in an incoherent strategy that has prevented it from undermining PAS's burgeoning popularity.